2016
DOI: 10.1177/0300060516652751
|View full text |Cite
|
Sign up to set email alerts
|

Distance from Dura mater to spinal cord at the thoracic vertebral level: An introductory study on local subdural geometry for thoracic epidural block

Abstract: ObjectiveTo evaluate the anatomical safety margins in relation to thoracic epidural block by analysing magnetic resonance (MR) images.MethodsThis retrospective study identified consecutive patients who underwent MR imaging of the thoracic vertebral spine. The distance from the dura mater to the spinal cord (DTC) was measured at different thoracic intervertebral levels using three different pathways as references: the ‘U’, ‘L’ and ‘M’ lines.ResultsA total of 346 patients provided MR images for analysis. The ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Although the ligamentum flavum is softer in children, loss of resistance is the most common method used to identify the epidural space at the thoracic and lumbar level in both children and adults . The anatomical dimensions related to epidural analgesia, including the dura to spinal cord distance at different vertebral levels, are not uniform . Several studies have investigated the dura to spinal cord distance in the thoracic region in adults and have reported that this particular distance was significantly greater in the middle thoracic region than at the upper and lower thoracic levels .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the ligamentum flavum is softer in children, loss of resistance is the most common method used to identify the epidural space at the thoracic and lumbar level in both children and adults . The anatomical dimensions related to epidural analgesia, including the dura to spinal cord distance at different vertebral levels, are not uniform . Several studies have investigated the dura to spinal cord distance in the thoracic region in adults and have reported that this particular distance was significantly greater in the middle thoracic region than at the upper and lower thoracic levels .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Several studies have investigated the dura to spinal cord distance in the thoracic region in adults and have reported that this particular distance was significantly greater in the middle thoracic region than at the upper and lower thoracic levels. 5,6 The dura to spinal cord distance may be a critical factor in avoiding neurological injury caused by needle trauma after dural puncture, with a greater dura to spinal cord distance increasing the potential safety margin. 5 When compared to computed tomography (CT), magnetic resonance imaging (MRI) is a superior modality in identifying injuries to the posterior longitudinal ligament and interspinous soft tissues, and remains the method of choice for assessing spinal cord lesions and ligamentous injury.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We already showed that duroplasty significantly reduces ISP after TSCI by enlarging the CSF space around the injured cord [ 12 ]. The higher ISP with conus medullaris injuries is likely related to the reduced CSF space around the conus medullaris compared with the larger CSF space higher up the spine [ 26 ]. The next factor that correlates with lower ISP is older age, perhaps because of cord atrophy in older patients, analogous to age-related brain atrophy [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%